2022
DOI: 10.3389/fneur.2022.959531
|View full text |Cite
|
Sign up to set email alerts
|

High systemic immune-inflammation index is associated with carotid plaque vulnerability: New findings based on carotid ultrasound imaging in patients with acute ischemic stroke

Abstract: Vulnerable carotid plaque is closely related to the occurrence of Ischemic stroke. Therefore, accurate and rapid identification of the nature of carotid plaques is essential. AS is a chronic immune inflammatory process. Systemic immune-inflammation index (SII) is a novel index of immune inflammation obtained from routine whole blood cell count analysis, which comprehensively reflects the state of inflammation and immune balance in the body. This study sought to explore the relationship between SII level and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Moreover, partial correlation analysis controlling for sex, age, BMI, and duration of diabetes demonstrated that SII was positively associated with apoB/A, FBG, PBG, HbA1c, GE index, poor glycaemic control, METS-IR, and inversely correlated with TC and HDL-C, suggesting that SII might be correlated with metabolic disorders, especially IR, hyperglycemia, and dyslipidaemia, and metabolic disorders might at least partially mediate the relationship between SII and DKD. Our findings were consistent with previous studies that reported the potential relationship between SII and metabolic disorders (70)(71)(72)(73)(74)(75)(76)(77)(78)(79). Some studies have demonstrated that the subjects with the highest quartile of SII have significantly higher homeostatic model assessment index of IR (HOMA-IR) than those with the lower quartiles in perimenopausal and postmenopausal women (70, 71), and the U.S. general population (72), and SII was positively associated with HOMA-IR in children with obesity (15).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, partial correlation analysis controlling for sex, age, BMI, and duration of diabetes demonstrated that SII was positively associated with apoB/A, FBG, PBG, HbA1c, GE index, poor glycaemic control, METS-IR, and inversely correlated with TC and HDL-C, suggesting that SII might be correlated with metabolic disorders, especially IR, hyperglycemia, and dyslipidaemia, and metabolic disorders might at least partially mediate the relationship between SII and DKD. Our findings were consistent with previous studies that reported the potential relationship between SII and metabolic disorders (70)(71)(72)(73)(74)(75)(76)(77)(78)(79). Some studies have demonstrated that the subjects with the highest quartile of SII have significantly higher homeostatic model assessment index of IR (HOMA-IR) than those with the lower quartiles in perimenopausal and postmenopausal women (70, 71), and the U.S. general population (72), and SII was positively associated with HOMA-IR in children with obesity (15).…”
Section: Discussionsupporting
confidence: 93%
“…In patients with HT, Çırakoğlu et al 45 demonstrated that SII is an independent predictor of increased carotid intima-media thickness. Zhang et al 46 showed a relationship between SII and vulnerable plaques in patients with acute ischemic stroke. Keskin et al 12 demonstrated that in stented patients receiving treatment for CAS, SII could be independently linked with short- and long-term clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Zhang’s study showed that a high SII may adversely affect carotid plaque vulnerability. Specifically, patients with fragile plaques with burst fibrous caps may experience a considerable impact, which might worsen the severity of AIS ( 35 ). A previous study based on the MIMIC-IV database showed that a high SII increased 30-day all-cause mortality ( 36 ).…”
Section: Discussionmentioning
confidence: 99%